Factors contributing to fidelity in a pilot trial of individualized resistant starches for pediatric inflammatory bowel disease: a fidelity study protocol - Castillo, Gisell; Mack, David R; Lalu, Manoj M; Singleton, Ruth; Fergusson, Dean A; Stintzi, Alain; Harrison, Megan; Presseau, Justin (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background The consumption of resistant starches is a promising adjuvant therapy for patients with inflammatory bowel disease. Rigorous evaluation of resistant starches in this setting depends on the intervention being delivered, received, and enacted as intended, that is, with fidelity. As part of a planned pilot trial, participants will be randomized to ingest resistant starches or a placebo. They will also be asked to collect stool samples and keep symptom and dose diaries to inform trial outcomes. We aim to identify potential factors impacting fidelity to the receipt and enactment of trial intervention and data collection activities from the perspective of patients and caregivers in the trial. Identifying fidelity barriers and enablers at the pilot trial phase of a clinical intervention may help to determine optimization processes when expanding to multiple sites in future trials. Methods We will conduct 15-30 semi-structured interviews with pilot trial participants (aged 8-17) and their caregivers. Trial participants will be approached for interviews approximately 6 months after the start of their trial participation. Personal projects analysis, a tool for understanding how individuals manage competing demands in their daily lives, will guide an in-depth exploration of how trial participants engage in activities related to intervention and data collection fidelity (ingesting resistant starches or placebo, collecting stool samples, keeping a symptom and dose diary) amidst the complexities of daily living. Discussion The present study will seek to explore and demonstrate how theory-informed fidelity assessments can be conducted alongside pilot trials to inform future multisite trials. Study results will clarify what factors may affect fidelity to trial intervention and data collection activities. Results may suggest what to modify to optimize the design and conduct, and ensure the integrity, of future multisite trials. Conducting process evaluations alongside clinical trials has the potential to improve our understanding of trial participant experiences. Results will provide a better understanding of how trial participants manage to engage in necessary trial activities along with other priorities.